Synaptic Assembly and Neural Circuit Development - Jaewon Ko (Frontiers Research Topics, 2018)
Synapses are fundamental signaling units of the central nervous system that mediate communication between individual neurons, participate in the computation of neuronal networks, and process information through long-term modification of their strength and structure. The normal function of the central nervous system critically depends on the establishment of 'precise' synaptic connections between neurons and specific target cells. During synaptogenesis, synapses form, mature, stabilize, and are eliminated through processes that require intimate communication between pre- and postsynaptic partners. The sequential and/or parallel processes dictate the wiring of neural circuits in a rapid and dynamic fashion. Accumulating evidence suggests that activity-dependent synaptic and circuit plasticity reflects the assembly and disassembly of diverse synapses that occur in a distinctive manner in specific neuron types. In this Research Topic, our purpose is to compile the latest developments in our understanding of molecular and cellular mechanisms underlying pre- and postsynaptic assembly, specification of synaptic adhesion pathways, presynaptic neurotransmitter release and postsynaptic receptor trafficking. In addition, non-neuronal cell processes involved in dismantling and eliminating synapses and relevant neural circuits will be covered. Clinical implications of this research topic will be considered, emphasizing the importance of these basic neuroscience research activities for translational and therapeutic applications. This includes literature describing recent methodologies for probing key issues regarding assembly/disassembly of synapses and circuits as well as primary research articles that provide critical insights into these fundamental questions in various model systems and experimental preparations.